Should India invest more in less-favored areas? - Fan, Shenggen; Hazell, Peter B. R. (International Food Policy Research Institute, 1997)
Developing countries have to allocate limited government resources for rural areas among different investment activities and regions to achieve the twin goals of productivity growth and poverty alleviation. This is particularly important at a time when many countries are facing severe financial constraints. This paper develops a framework and provides empirical evidence on the impact of government investments in technology, irrigation, education and infrastructure on agricultural productivity growth and rural poverty reduction in rural India. The results reveal that government investments in more favored areas played significant roles during the green revolution period. But the marginal returns from additional government investments in these areas have declined in more recent years. It is now the less-favored areas where marginal returns are higher. This result has important policy implications for where government investments should be targeted in order to achieve further productivity growth and rural poverty reductions.